Lithium ion battery with high rate capability and preparation method thereof

By using graphene array-coated aluminum foil and conductive additives to form a three-dimensional network structure with conjugated polycarbonyl polymers in lithium-ion batteries, the problems of capacity decay and heat accumulation in lithium-ion batteries under high-rate conditions are solved, achieving higher charge-discharge efficiency and energy density.

CN120878759APending Publication Date: 2025-10-31NAT UNIV OF SCI & TECH CHONGQING COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510760131.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing lithium-ion batteries suffer from capacity decay, voltage drop, and heat accumulation under high-rate conditions, affecting their lifespan and performance. This is especially true in applications such as electric vehicles, where there is a need to improve the rate characteristics of lithium-ion batteries.

Method used

Aluminum foil with a graphene array coating is used as a current collector, and conductive agents and conjugated polycarbonyl polymer particles are added to the positive electrode to form a three-dimensional network conductive structure, thereby improving the efficiency of electron and ion transport.

Benefits of technology

It significantly improves the high-rate cycle performance of lithium-ion batteries, enhances the electron transport process of electrode materials, and achieves faster charge and discharge capabilities and higher energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120878759A_ABST
    Figure CN120878759A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery with high rate capability, which comprises a positive pole piece with a continuous three-dimensional conductive network structure, and the positive pole piece comprises a current collector of an aluminum foil with a graphene coating, a conductive additive and an organic active electrode material. The invention also discloses a preparation method of the lithium ion battery with high rate capability. According to the lithium ion battery, the conductive additive with a multi-dimensional structure is fully mixed with the conjugated multi-carbonyl polymer to form an effective three-dimensional network conductive structure, and the graphene array coating aluminum foil is combined as a current collector to construct a continuous three-dimensional conductive network structure, so that the electron transmission process of an electrode material is obviously improved, and the performance of the lithium ion battery is improved. And meanwhile, more lithium ions are driven to be embedded / separated, so that rapid and effective transmission of the lithium ions is realized, and the excellent rate characteristic is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy materials technology, specifically relating to a lithium-ion battery with high rate performance and its preparation method. Background Technology

[0002] Energy is the driving force behind global development and economic growth, and a fundamental guarantee for human survival. With rapid economic development and a surge in population, human demand for energy continues to rise. However, fossil fuels such as coal, oil, and natural gas are increasingly depleted, and problems such as global warming and ecological degradation are becoming increasingly prominent. Developing new energy sources is an inevitable requirement for achieving sustainable economic development. New energy sources such as wind, solar, and tidal energy have advantages such as being renewable, widely distributed, and pollution-free, but they also suffer from instability, dispersed energy density, intermittency, and difficulty in direct use, requiring conversion into secondary energy sources for utilization. Therefore, exploring efficient and safe energy storage technologies has become a key focus of society. Lithium-ion batteries, with their high energy utilization rate, flexible use, and fast response speed, are widely used in electric vehicles, aircraft, smart grids, and consumer electronics. Especially in the current era where electric and hybrid vehicles are gradually replacing gasoline vehicles, the demand for high-rate performance lithium-ion batteries has surged.

[0003] The rate capability of lithium-ion batteries is one of the most critical parameters for high-power batteries. Specifically, it refers to the charge and discharge capacity and speed, which involves the battery's performance at different charge and discharge rates. High-rate lithium-ion batteries can achieve higher energy density and lower internal resistance at higher rates, thereby greatly shortening the charging time and greatly promoting the application of lithium-ion batteries in electric vehicles (EVs). However, under high-rate conditions, lithium-ion batteries may experience significant capacity decay, leading to reduced range; the battery's output voltage may decrease, resulting in a reduction in energy density; in addition, high-rate charging and discharging may cause a large amount of heat to be generated in the lithium-ion battery. The accumulation of heat inside the lithium-ion battery will lead to an increase in temperature and a large temperature gradient, causing internal performance degradation and affecting the lifespan of the lithium-ion battery. The main factors affecting the rate capability of lithium-ion batteries can be divided into: (1) the rate capability of electrode materials; (2) the battery's operating temperature; and (3) the battery's internal impedance.

[0004] In lithium-ion batteries, Li +The transmission of ions is a slow process. If the ion transport channel is blocked, it will cause significant polarization and an increase in internal impedance. On the other hand, during the charging process of lithium-ion batteries, the migration of electrons is inevitably accompanied by the insertion or extraction of lithium ions. If electrons cannot be input or output in time, the locally enriched electrons will also limit the insertion or extraction of lithium ions, ultimately resulting in the electrode material's capacity not being fully utilized. Therefore, improving the rate performance of lithium-ion batteries ultimately comes down to constructing the internal ion and electron transport paths of the battery and increasing the transport rate. Improving the rate performance of lithium-ion batteries usually involves several aspects of optimization: (1) Electrode design optimization, that is, optimizing the electrode structure and materials to increase the electrode surface area and the rate of ion diffusion. Using nanomaterials, porous materials or three-dimensional electrode structures can improve the rate performance of electrodes and develop fast-charging materials with high ion conductivity and fast diffusion rate for use in the positive and negative electrodes of batteries; (2) Electrolyte optimization: improve the composition and properties of electrolytes, select electrolytes with high ion conductivity and low impedance to facilitate faster ion transport between positive and negative electrodes; (3) Adding additives: add some additives to the electrolyte, such as conductivity agents or anti-dendrying additives, to help reduce the dendrite growth of lithium ions, thereby improving the rate performance; (4) Interface improvement: improve the interface between the electrode and the electrolyte, reduce resistance, and promote ion and electron conduction. Research has shown that constructing a three-dimensional transport network through 3D electrode structures significantly improves the electron transport process of electrode materials (ACS Energy Lett. 2023, 8, 2522-2531). Furthermore, increasing the electronic conductivity of electrode materials can increase the effective voltage applied to the bulk phase of the electrode material, driving more lithium-ion insertion / extraction, thereby achieving excellent rate performance (Angew. Chem. Int. Ed. 2023, 62, e202218595). Therefore, finding a material and technology that can effectively improve the rate performance and other comprehensive properties of lithium-ion batteries is an urgent problem to be solved. Summary of the Invention

[0005] This invention aims to at least partially solve one of the technical problems in related technologies. Therefore, the main objective of this invention is to provide a lithium-ion battery with high-rate performance and its preparation method. This method utilizes an aluminum foil with a graphene array coating as the current collector, adds a conductive agent during the preparation of the positive electrode, and effectively mixes the conductive agent with conjugated polycarbonyl polymer particles from the lithium-ion battery to form a three-dimensional network conductive structure in the positive electrode. This fully leverages the high-capacity characteristics of the conjugated polycarbonyl polymer while simultaneously achieving efficient electron transfer during charging and discharging, significantly improving the high-rate cycle performance of the lithium-ion battery.

[0006] The objective of this invention is achieved through the following technical solution: A lithium-ion battery with high rate performance includes a positive electrode with a continuous three-dimensional conductive network structure.

[0007] In some specific embodiments, the positive electrode includes a current collector of aluminum foil with a graphene coating, as well as conductive additives and organic active electrode materials.

[0008] In some specific embodiments, the aluminum foil with graphene coating consists of graphene nanosheets arranged radially and vertically on the aluminum foil current collector, with a coating thickness of 0.1-5 μm.

[0009] In some specific embodiments, the conductive additive includes, but is not limited to, one or more of point-type, linear, surface-type, and 3D structural conductive additives.

[0010] Furthermore, the conductive additives include, but are not limited to, one or more of conductive carbon black, conductive super carbon, single-walled carbon nanotubes, multi-walled carbon nanotubes, single-layer graphene, multi-layer graphene, graphite, and three-dimensional foamed carbon.

[0011] In some specific embodiments, the organic active electrode material is a conjugated polycarbonyl polymer.

[0012] Furthermore, the molecular structural formula of the conjugated polycarbonyl polymer is as follows: .

[0013] In some specific embodiments, the mass ratio of the organic active electrode material to the conductive additive is (4-6):(3-5).

[0014] In some specific embodiments, the positive electrode sheet is prepared by the following method, specifically including the following steps: S1: Mix the organic active electrode material, conductive additives, binders and organic solvents evenly into a slurry according to the formula requirements; S2: The slurry prepared in S1 is coated onto an aluminum foil with a graphene coating by a scraper with a thickness of 60-90 μm to obtain a pre-electrode. S3: The pre-electrode prepared in S2 is initially dried at 40-60℃ for 3-5 hours, then dried under vacuum at 100-135℃ for 18-24 hours, and cut into electrode sheets with a diameter φ of 10-20 mm to obtain the positive electrode sheet.

[0015] Belonging to the same concept as this invention, this invention also provides a method for preparing the lithium-ion battery with high rate performance, which involves using the positive electrode as the positive electrode, a lithium sheet as the negative electrode, adding a separator and an electrolyte, and assembling a coin-type lithium-ion battery in a glove box under an argon atmosphere to obtain a lithium-ion battery with high rate performance.

[0016] Compared with the prior art, the present invention has at least the following advantages: 1) The high-rate performance lithium-ion battery provided by this invention employs a multi-dimensional conductive additive and a conjugated multi-carbonyl polymer to fully mix and form an effective three-dimensional network conductive structure. Combined with a graphene array-coated aluminum foil as a current collector, a continuous three-dimensional conductive network structure is constructed. This improves the interfacial contact with the positive electrode, increases conductive contact sites, and enhances the conductivity of the battery structure. Furthermore, it improves the interface between the electrode and the electrolyte, reduces resistance, and promotes ion and electron conduction. This invention significantly improves the electron transport process of the electrode material by constructing a three-dimensional transport network through the three-dimensional network electrode structure, simultaneously driving more lithium ions to insert / extract, achieving rapid and efficient lithium ion transport, thereby achieving excellent rate performance.

[0017] 2) The lithium-ion battery of the present invention is simple to operate, easy to control, highly feasible, and uses inexpensive raw materials, making it suitable for industrial production. Attached Figure Description

[0018] To more clearly illustrate the specific embodiments of the present invention, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.

[0019] Figure 1 The synthetic route for the organic active electrode material BQ1-COF prepared in this invention is shown below. Figure 2 The nuclear magnetic resonance spectrum of the organic active electrode material BQ1-COF prepared in this invention is shown. Figure 3 The charge-discharge curves of the lithium-ion battery prepared in Example 1 during the first three weeks; Figure 4 The rate performance curve of the lithium-ion battery prepared in Example 1; Figure 5 The rate performance curve for Example 2; Figure 6 The rate performance curve for Example 3; Figure 7 The rate performance curve for Example 4; Figure 8 The rate performance curve for Example 5; Figure 9 The rate performance curve of the lithium-ion battery prepared for Comparative Example 1 is shown. Detailed Implementation

[0020] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The following embodiments are merely descriptive and not limiting, and should not be construed as limiting the scope of protection of the present invention.

[0021] When a quantity, concentration, or other value or parameter is described as a range, preferred range, or preferred upper and lower limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper or preferred values ​​with any lower or preferred values, regardless of whether the range is specifically disclosed. Unless otherwise stated, the numerical range values ​​listed herein include the endpoints of the range and all integers and fractions within that range.

[0022] Unless otherwise stated, all percentages, parts, ratios, etc. in this document are by weight.

[0023] The materials, methods, and embodiments described herein are exemplary and should not be construed as limiting unless otherwise stated.

[0024] In the following examples, cyclohexanehexaone octahydrate (HAT) was an analytical grade reagent purchased from Shanghai Boka Chemical Technology Co., Ltd.; tetraaminobenzoquinone (TABQ) was a chemically pure reagent purchased from Jilin Zhongke Kexin Technology Co., Ltd.; the solvent deoxynoxy N-methyl-2-pyrrolidone (NMP) was an anhydrous analytical grade reagent; sulfuric acid, ethanol, methanol, and other reagents were provided by Shanghai Titan Reagent Co., Ltd. and used directly; MWCNTs were provided by Chengdu Organic Chemistry Co., Ltd. of the Chinese Academy of Sciences; and CB (Kelode Reagent, LiTX200), SP (Kelode Reagent, Super C45), CMK-3 (Nanjing Momentum Materials Technology Co., Ltd.) and Graphene (Chengdu Zhongke Shidai Nano Energy Technology Co., Ltd.) could all be purchased commercially; the binder polyvinylidene fluoroethylene (PVDF), solvents DME and DOL, and lithium salt LiTFSI were all purchased by Shanghai Titan Reagent Co., Ltd. and used directly.

[0025] The test methods used in the following embodiments include: The structure and electrochemical performance of the electrode material are demonstrated by testing the main properties of each test sample separately; the main properties tested in this application include 1 H NMR, charge-discharge curves for the first three weeks, rate performance at different current densities, etc. 1 The H NMR instrument was a Quantum-I Plus 600MHz, using DMSO as the solvent; charge / discharge and rate performance tests were performed using the LAND battery testing system, model CT2001A, manufactured by Wuhan LAND Electronics Co., Ltd.

[0026] Example 1 The method for preparing lithium ions with high rate capability provided in this embodiment includes the following steps: 1) Preparation of organic active electrode material BQ1-COF The preparation process of the organic active electrode material in this application is as follows: Figure 1 As shown, cyclohexanehexane octahydrate (HAT, 624 mg, 2 mmol) and tetraaminobenzoquinone (TABQ, 504 mg, 3 mmol) were added to a reaction tube. Argon gas was slowly added to deoxy-N-methyl-2-pyrrolidone (NMP, 20 mL) and 5 drops of sulfuric acid. The mixture was heated to 65 °C overnight. The resulting precipitate was filtered, washed with a large amount of methanol and deionized water, and then further extracted with deionized water and ethanol (1:1 v / v) using the Soxhlet method. Finally, the prepared product was vacuum dried at 80 °C overnight to obtain the organic active electrode material BQ1-COF. The prepared product was subjected to nuclear magnetic resonance (NMR) testing, and its NMR spectrum is shown below. Figure 2 As shown, from Figure 2 It is evident that this application successfully synthesized a conjugated polycarbonyl polymer.

[0027] 2) Preparation of graphene array coated current collector A graphene array coating current collector was prepared on the surface of aluminum foil using an RF-PECVD system. The RF power was 50W, the chamber pressure was 50Pa, a mixture of methane and hydrogen was introduced into the chamber, the CH4:H2 gas flow rate ratio was 6:4, the growth temperature was 450℃, and the growth time was 20min, thus obtaining the graphene array coating current collector.

[0028] 3) Preparation of lithium-ion batteries The organic active electrode material prepared in step 1), the linear conductive additive multi-walled carbon nanotubes (MWCNTs), and PVDF (polyvinylidene fluoride) were mixed and stirred evenly in a mass ratio of 5:4:1 to prepare a slurry, wherein the solvent was NMP. This slurry was coated onto the current collector prepared in step 2), dried at 120℃ for 12 hours, and then cut into electrode sheets with a diameter of 12 mm. A density of 6 mg / cm³ was selected. 2 The electrode is the organic positive electrode of a lithium-ion battery.

[0029] The organic cathode of the lithium-ion battery prepared in this embodiment was subjected to electrical performance testing. Specifically, the battery was assembled in a glove box under an argon atmosphere. The electrolyte was 2.0M LiTFSI in DME:DOL=1:1 Vol% with 1% LiNO3, and the separator was a 2325 separator. The electrochemical performance of the battery was tested using a LAND-CT3001A tester. The current was set to 0.1C, 0.5C, 2C, and 5C, and the voltage range was set to 1.2V to 3.5V.

[0030] The results are as follows Figure 3 and Figure 4 As shown, from Figure 3As can be seen from the data, the organic active electrode material BQ1-COF in Example 1 exhibits excellent specific capacity, reaching 740 mAh / g in the first cycle; the discharge capacities in the second and third cycles are 500 mAh / g and 420 mAh / g, respectively. Irreversible charge-discharge capacity occurs in the first cycle due to interfacial side reactions and SEI formation, but excellent cycle reversibility is observed in the second and third cycles.

[0031] from Figure 4 As can be seen, the organic active electrode material in this embodiment exhibits excellent rate performance and cycle reversibility. Even when the density reaches a high rate of 5C, it still maintains a specific capacity of over 180 mAh / g, indicating that the electrode material has good electrochemical performance.

[0032] Example 2 The comparative example provides a method for preparing lithium ions with high rate capability, which includes the following steps: 1) Preparation of organic active electrode material BQ1-COF Same as Example 1; 2) Preparation of graphene array coated current collector A graphene array coating current collector was prepared on the surface of aluminum foil using an RF-PECVD system. The RF power was 50W, the chamber pressure was 50Pa, a mixture of methane and hydrogen was introduced into the chamber, the CH4:H2 gas flow rate ratio was 6:4, the growth temperature was 450℃, and the growth time was 20min, thus obtaining the graphene array coating current collector. 3) Preparation of lithium-ion batteries The above-mentioned organic active electrode material, conductive carbon black (CB) and PVDF were mixed and stirred evenly in a mass ratio of 5:4:1 to prepare a slurry, wherein the solvent was NMP; the slurry was coated on the above-mentioned current collector, dried at 120°C for 12 hours, and then cut into electrode sheets with a diameter of 12 mm and a density of 6 mg / cm³. 2 The electrode is the organic positive electrode of a lithium-ion battery.

[0033] Example 3 The comparative example provides a method for preparing lithium ions with high rate capability, which includes the following steps: 1) Preparation of organic active electrode material BQ1-COF Same as Example 1; 2) Preparation of graphene array coated current collector This invention uses an RF-PECVD system to prepare a graphene array coating current collector on the surface of an aluminum foil. The RF power is 50W, the chamber pressure is 50Pa, a mixture of methane and hydrogen is introduced into the chamber, the CH4:H2 gas flow rate ratio is 6:4, the growth temperature is 450℃, and the growth time is 20min, thus obtaining a graphene array coating current collector. 3) Preparation of lithium-ion batteries The above-mentioned organic active electrode material, point-type conductive additive carbon black (SP), and PVDF were mixed and stirred evenly in a mass ratio of 5:4:1 to prepare a slurry, wherein the solvent was NMP; the slurry was coated onto the above-mentioned current collector, dried at 120°C for 12 hours, and then cut into electrode sheets with a diameter of 12 mm. A density of 6 mg / cm³ was selected. 2 The electrode is the organic positive electrode of a lithium-ion battery; Example 4 The comparative example provides a method for preparing lithium ions with high rate capability, which includes the following steps: Preparation of organic active electrode material BQ1-COF Same as Example 1; Preparation of graphene array coated current collectors This invention uses an RF-PECVD system to prepare a graphene array coating current collector on the surface of an aluminum foil. The RF power is 50W, the chamber pressure is 50Pa, a mixture of methane and hydrogen is introduced into the chamber, the CH4:H2 gas flow rate ratio is 6:4, the growth temperature is 450℃, and the growth time is 20min, thus obtaining a graphene array coating current collector. 3) Preparation of lithium-ion batteries The above-mentioned organic active electrode material, three-dimensional composite conductive additive conductive carbon black (CB) + ordered mesoporous carbon (CMK-3) and PVDF were mixed and stirred evenly at a mass ratio of 5:4:1 to prepare a slurry, wherein the solvent was NMP; the slurry was coated on the above-mentioned current collector, dried at 120℃ for 12h, and then cut into electrode sheets with a diameter of 12mm. A density of 6mg / cm³ was selected. 2 The electrode is the organic positive electrode of a lithium-ion battery; Example 5 The comparative example provides a method for preparing lithium ions with high rate capability, which includes the following steps: Preparation of organic active electrode material BQ1-COF Same as Example 1; Preparation of graphene array coated current collector This invention uses an RF-PECVD system to prepare a graphene array coating current collector on the surface of an aluminum foil. The RF power is 50W, the chamber pressure is 50Pa, a mixture of methane and hydrogen is introduced into the chamber, the CH4:H2 gas flow rate ratio is 6:4, the growth temperature is 450℃, and the growth time is 20min, thus obtaining a graphene array coating current collector. 3) Preparation of lithium-ion batteries The above-mentioned organic active electrode material, three-dimensional composite conductive additive conductive carbon black (CB) + graphene, and PVDF were mixed and stirred evenly at a mass ratio of 5:4:1 to prepare a slurry, wherein the solvent was NMP; the slurry was coated on the above-mentioned current collector, dried at 120℃ for 12 hours, and then cut into electrode sheets with a diameter of 12 mm and a density of 6 mg / cm³. 2 The electrode is the organic positive electrode of a lithium-ion battery; The lithium-ion batteries prepared in Examples 2-5 were subjected to electrochemical performance tests. Specifically, the batteries were assembled in a glove box under an argon atmosphere. The electrolyte was 2.0M LiTFSI in DME:DOL=1:1 Vol% with 1% LiNO3, and the separator was a 2325 separator. The electrochemical performance of the batteries was tested using a LAND-CT3001A tester. The currents were set to 0.1C, 0.5C, 2C, and 5C, and the voltage range was set to 1.2V to 3.5V.

[0034] This application also conducted performance tests on the lithium-ion batteries prepared using different conductive additives in Examples 2-5, and the results are as follows: Figure 5-8 As shown, from Figure 5 It can be seen that when the conductive additive is changed from linear conductive agents (MWCNTs) to zero-dimensional conductive agents (conductive carbon black CB), the rate performance of the organic active electrode material BQ1-COF shows a certain degree of decay. When the current density reaches 5C, it shows a specific capacity of 175mAh / g, indicating that different types of conductive additives have a certain impact on the rate performance of this electrode material.

[0035] To further verify the effect of different types of conductive additives on rate performance, this application also used zero-dimensional point-type (SP) conductive additives (SPs) respectively. Figure 6 ), zero-dimensional conductive additives and one-dimensional conductive additives (CB+CMK-3) composite conductive agent ( Figure 7 ), zero-dimensional conductive additives and two-dimensional conductive additives (CB+Graphene) composite conductive agent ( Figure 8In comparison, at a current density of 5C, the specific capacities exhibited were 55 mAh / g, 130 mAh / g, and 120 mAh / g, respectively. The study shows that compared to linear conductive additives (MWCNTs), the electrochemical performance of other conductive agents all exhibits a certain degree of degradation. In this invention, the optimal conductive additive for the organic active electrode material BQ1-COF is linear MWCNTs.

[0036] Comparative Example 1 This comparative example provides a method for preparing lithium-ion batteries with high rate capability. Step 1) is the same as in Example 1, except that step 2) is omitted, i.e., the graphene array coating current collector is not prepared, and aluminum foil is used directly as the current collector. Specifically: The organic active electrode material prepared in step 1), the linear conductive additive MWCNT, and PVDF (polyvinylidene fluoride) were mixed and stirred evenly in a mass ratio of 5:4:1 to prepare a slurry, wherein the solvent was NMP. The slurry was coated onto an aluminum foil current collector and dried at 120℃ for 12 hours. Electrodes with a diameter of 12 mm and a density of approximately 6 mg / cm³ were then selected. 2 The electrode is the organic positive electrode of a lithium-ion battery.

[0037] This application conducts performance tests on the lithium-ion battery prepared in Comparative Example 1. The specific test method is as follows: the battery is assembled in a glove box under an argon atmosphere. The electrolyte is 2.0M LiTFSI in DME:DOL=1:1 Vol% with 1% LiNO3, and the separator is a 2325 separator. The electrochemical performance of the battery is tested using a LAND-CT3001A tester. The current is set to 0.1C, 0.5C, 2C, and 5C, and the voltage range is set to 1.2V to 3.5V.

[0038] Test results are as follows Figure 9 As shown in the figure, when the current density reaches 5C, it exhibits a specific capacity of 85 mAh / g. The difference between it and Example 1 is whether the current collector contains a graphene array coating. By comparing the performance, it can be seen that the electrochemical performance in Example 1 is better, indicating that the current collector coated with graphene array is more conducive to high rate performance.

[0039] In summary, the preparation method provided in this application, by employing a modified graphene-coated current collector and adding conductive additives during the preparation of the positive electrode sheet, can effectively mix with the organic active electrode material particles in the lithium-ion battery, forming a continuous three-dimensional network conductive structure in the positive electrode sheet. This greatly improves the conductivity of the organic active electrode material, further enhances the specific capacity of the organic active electrode material, and simultaneously achieves effective electron transfer during charging and discharging, thus realizing the optimal rate performance of the lithium-ion battery.

[0040] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. A lithium-ion battery with high rate performance, characterized in that, This includes positive electrode sheets with a continuous three-dimensional conductive network structure.

2. The lithium-ion battery with high rate performance according to claim 1, characterized in that, The positive electrode includes a current collector with an aluminum foil having a graphene coating, as well as conductive additives and organic active electrode materials.

3. The lithium-ion battery with high rate performance according to claim 2, characterized in that, The aluminum foil with graphene coating consists of graphene nanosheets arranged radially and vertically on the aluminum foil current collector, with a coating thickness of 0.1-5 μm.

4. The lithium-ion battery with high rate performance according to claim 2, characterized in that, The conductive additives include, but are not limited to, one or more of the following: point-type, linear, surface-type, and 3D structural conductive additives.

5. The lithium-ion battery with high rate performance according to claim 4, characterized in that, The conductive additives include, but are not limited to, one or more of the following: conductive carbon black, conductive super carbon, single-walled carbon nanotubes, multi-walled carbon nanotubes, single-layer graphene, multi-layer graphene, graphite, and three-dimensional foamed carbon.

6. The lithium-ion battery with high rate performance according to claim 2, characterized in that, The organic active electrode material is a conjugated polycarbonyl polymer.

7. The lithium-ion battery with high rate performance according to claim 6, characterized in that, The molecular structural formula of the conjugated polycarbonyl polymer is as follows: 。 8. The lithium-ion battery with high rate performance according to claim 1, characterized in that, The mass ratio of the organic active electrode material to the conductive additive is (4-6):(3-5).

9. The lithium-ion battery with high rate performance according to any one of claims 1-8, characterized in that, The positive electrode sheet is prepared by the following method, specifically including the following steps: S1: Mix the organic active electrode material, conductive additives, binders and organic solvents evenly into a slurry according to the formula requirements; S2: The slurry prepared in S1 is coated onto an aluminum foil with a graphene coating by a scraper with a thickness of 60-90 μm to obtain a pre-electrode. S3: The pre-electrode prepared in S2 is initially dried at 40-60℃ for 3-5 hours, then dried under vacuum at 100-135℃ for 18-24 hours, and cut into electrode sheets with a diameter φ of 10-20 mm to obtain the positive electrode sheet.

10. A method for preparing a lithium-ion battery with high rate performance according to any one of claims 1-9, characterized in that, By using the aforementioned positive electrode as the positive electrode, a lithium sheet as the negative electrode, and adding a separator and electrolyte, a button-type lithium-ion battery is assembled in a glove box under an argon atmosphere, thus obtaining a lithium-ion battery with high rate performance.